NGHIÊN CỨU ẢNH HƯỞNG CỦA MỘT SỐ PHỤ GIA BÊ TÔNG ĐẾN ĂN MÒN CỐT THÉP TRONG MÔI TRƯỜNG NƯỚC BIỂN - Bùi, Đình Huy; Bùi, Bá Xuân; Lưu, Hoàng Tâm; Nguyễn, Bá Tài; Phan, Bá Tứ (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
A STUDY ON THE EFFECTS OF SOME CONCRETE ADDITIVIES ON REBAR CORROSION IN SEA WATER In the study naturaltests of reinforced concrete samples contained corrosion inhibitors including sodium silicate, urea, thiourea (in the concentrations: 0, 0.05, 0.10, 0.15 and 0.20%) and silica fume (in the volume of 0; 2.5, 5.0, 7.5 and 10%) in the Vietnam tropical sea have been carried out and the effects of depth and their nature and concentration on the corrosion behavior of Pomina and Vina carbon steels embedded in concrete after 01 month of testing were investigated. It is found that the corrosion protection effectiveness (η) of the four inhibitors are η (Thiourea) > η (Urea) > η (Sodium silicate) > η (Silica fume). The steel-reinforced corrosion activity of the sea at the depth of 0.5 m was higher than that at the depth of 1m.